A comprehensive characterisation of beer polyphenols by high resolution mass spectrometry (LC–ESI-LTQ-Orbitrap-MS). (15th February 2015) - Quifer-Rada, Paola; Vallverdú-Queralt, Anna; Martínez-Huélamo, Miriam; Chiva-Blanch, Gemma; Jáuregui, Olga; Estruch, Ramon; Lamuela-Raventós, Rosa
Highlights: Phenolic profile of 4 types of beer has been analyzed by high resolution mass spectrometry. Phenolic profile among the four types of beers was very similar. 47 phenolic compounds were identified, 7 of them are described in beer for the first time. Abstract: Beer is the second most consumed alcoholic beverage in Europe and shown by the European Prospective Investigation into Cancer and Nutrition cohort study to be the main food contributor to hydroxybenzoic acid intake. About 70–80% of the total polyphenol content in beer comes from malt, and the remaining 30–20% from hops. In this work, liquid chromatography coupled with an electrospray ionization hybrid linear ion trap quadrupole Orbitrap mass spectrometry technique has been used for an accurate identification of beer polyphenols. 47 phenolic compounds were identified using high mass accuracy and confirmed by MS 2 experiments, including simple phenolic acids, hydroxycinnamoylquinics, flavanols, flavonols, flavones, alkylmethoxyphenols, alpha- and iso-alpha-acids, hydroxyphenylacetic acids and prenylflavonoids. As far as we know, 7 of these compounds have been recognised in beer for the first time: feruloylquinic acid, caffeic acid- O -hexoside, coumaric acid- O -hexoside, sinapic acid- O -hexoside, catechin- O -dihexoside, kaempferol- O -hexoside, and apigenin- C -hexoside-pentoside.